Multi-Level Policy Coherence Analysis in Wicked Nexus Problem Settings: The Case of Nitrogen Pollution in Germany - Mabel Ramisch; Sabrina Kirschke; Norbert Weber (Environmental Policy and Governance, 2025)
Environmental problems are often wicked and face multiple challenges, making policy coherence a goal of high relevance. The issue of nitrogen pollution is an outstanding example, representing the pressing demand on different policy fields and levels to achieve coherence of the respective objectives, instruments, and measures. However, policy coherence analysis often provides a horizontal perspective only and likely misses the opportunities a more complex analysis may reveal. This study provides a multi-level policy coherence analysis, focusing on emerging forest-related water protection measures as an example of multi-functional measures such as agroforestry systems or short rotation plantations. We analyze the degree of policy coherence across policy fields (agriculture, forestry, water protection) and political levels (Europe, Germany, Thuringia) based on a qualitative content analysis of policy objectives and instruments. Surprisingly, we find a high degree of policy coherence between the areas of interest on all political levels. However, incoherence is also present, especially between the policy fields of forestry and water in consideration of agriculture. Analytically, this study shows the importance of complex analyses to understand the ramifications of wicked nexus problems in multi-level governance systems. Overall, the results show valuable entry points from a multi-level policy coherence perspective.
Keywords: 330; agroforestry systems; multi-level governance; resource nexus; short rotation plantation; water quality; wicked problems